Myths on religions in Russian media: a functional perspective - Khroul Victor (Studia Humanitatis, 2023)
Considering the myth in the Platonic tradition as a surrogate replacement of the reasonable cause of some judgment or action, when the true cause is not understandable due to its complexity, the author describes the phenomenology of modern myths and their functioning in Russian media and public sphere. The paper is focused on two types of mythologizing of religion in media, related to the subject of coverage – internal, doctrinal, irrational or external, social, rational. Author suggests that from the normative point of view epistemological function of journalism presumes the rationalization of religious life coverage and “demythologizing” of socially dangerous myths related to the religious sphere.